Enquête Épidémiologique sur la Maladie Cœliaque dans la région d’El Oued. - MEGUERHI Abir (Université of Eloued, 2024)
The aim of the statistical study we conducted was to estimate the prevalence of celiac disease (MC) in the Valley region, through an oral questionnaire in which 698 people participated without choosing, where the prevalence rate in the studied sample was 0.7%. The main work consists of a written questionnaire covering 120 patients of both sexes suffering from MC is a chronic autoimmune disease and inflammatory enteropathy that occurs in people with a genetic predisposition to consuming gluten. According to the results of the questionnaire, the female/male ratio in the studied sample was (1.55/1) and their age ranged from one to 57 years, the percentage of children is 13.33%. The most affected age group is that of adults, with a rate of 86.67%, while 60% are thin, 4% are overweight and 57.5% have no family history. 95% were diagnosed by serological tests, 78,33% by histological tests and73,33% by the two tests combined, The classic form of the disease was predominant in the sample based on reported clinical symptoms of diarrhea, abdominal pain and bloating, anemia, etc. The application of RSG is the only treatment for this disease . the application rate of RSG in the sample was 98.33%, and the doctor is the primary source of RSG at 94.18%, and patients consider RSG difficult, 91.66% and 92.5% say it is effective, and patients consider the lack of food availability without gluten, their prices, their bad taste and the embarrassment which they consider to be the greatest difficulties from which they suffer. Finally, the early diagnosis and the strict application of the RSG remain the prevention and treatment of MC until now
Keywords: wilaya of El Oued; survey; Celiac disease; Gluten; Villous atrophy Prevalence; Gluten-free diet; Villous atrophy.